The Reference Group as Antecedent of Gray Market Participation: An Empirical Analysis. - Gimeno-Arias, Fernando; Santos Jaén, José Manuel; León-Gómez, Ana María (Taylor & Francis, 2023)
Purpose The objective of this research is to analyze the motivation of a distributor belonging to an official marketing channel to participate in the gray market. We explore this motivation not as an opportunistic behavior but as a strategic decision aligned with the reference group to which it belongs and the homogenization or isomorphism of strategic decisions within the group. Methodology/Approach Based on a survey of a sample of Spanish official distributors of Fast-Moving Consumer Goods (FMCG) and an empirical study using PLS-SEM, found evidence that the imitation effect conditions strategic decisions and can be graduated according to the hierarchical position occupied or legitimacy within the reference group. Findings The hypothesized model was supported by the data. This indicates that the reference group influences the agents that make it up and determines the actions expected of its members, offering a tool to the manufacturer or brand owner to manage the official distribution channel. Originality/Value The investigation of the effect of the reference group on the behavior of the official distributor offers an alternative to the classical explanation of its participation in the gray market, which has not been addressed by the academic literature so far, and which has traditionally been explained by the individual opportunism of the agents. Practical implications The main managerial implication is to provide a monitoring element to the official distribution channel leader, such as influencing the behaviors of the reference group to efficiently manage the marketing channel.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/42044
Keywords: Canales de distribución (Comercio); Marketing; Marketing channel; Gray market; Opportunism; Reference groups; Legitimacy